Pengaruh Senam Hamil terhadap Nyeri Punggung dan Kualitas Tidur pada Ibu Hamil Trimester Ketiga - Intan Ansori; Yanti Cahyanti; Dita Eka Mardiani; Ir Ir Khairiyah P; Sariestya Rismawati; Debby Syahru Romadlon (STIKes Persada Husada Indonesia, 2026)
Research Objective: This study aimed to examine changes in back pain levels and sleep quality following pregnancy exercise among third-trimester pregnant women. Methodology: This quantitative study used a pre-experimental one-group pretest-posttest design. The study was conducted in the working area of Cikoneng Health Center, Ciamis Regency, and involved 33 third-trimester pregnant women selected through purposive sampling. Back pain was assessed using the Numeric Rating Scale (NRS), and sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) before and after four structured pregnancy-exercise sessions over one month. Data were analyzed using the Wilcoxon signed-rank test. Results: Before the intervention, most respondents experienced moderate back pain and poor sleep quality. After the intervention, most respondents reported mild or no back pain, and sleep quality improved. The pretest-posttest differences were statistically significant (p < 0.001). Conclusion: Pregnancy exercise was associated with reduced back pain and improved sleep quality in this single-group preliminary study. The findings support its potential use as a complementary non-pharmacological approach in antenatal care, while controlled studies are still needed.